The Accounting Review (JSTOR)
The Accounting Review is the premier journal for publishing articles reporting the results of accounting research and explaining and illustrating related research methodology. The scope of acceptable articles embraces any research methodology and any accounting-related subject
Keywords: Business, Business & Economics